2015
DOI: 10.18632/oncotarget.3687
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-induced apoptosis prevents EBV infection

Abstract: Epstein-Barr virus (EBV) is a human gamma-1 herpesvirus that establishes a lifelong latency in over 90% of the world's population. During latency, virus exists predominantly as a chromatin-associated, multicopy episome in the nuclei of a variety of tumor cells derived from B cells, T cells, natural killer (NK) cells, and epithelial cells. Licorice is the root of Glycyrrhiza uralensis or G. glabra that has traditionally cultivated in eastern part of Asia. Licorice was reported to have anti-viral, anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 57 publications
1
50
0
1
Order By: Relevance
“…Quercetin, an aglycone of rutin, is a phytochemical abundant in plants and may diminish the replication of many viruses: highly pathogenic influenza virus [50], rhinovirus [51], dengue virus type-2 [52], HSV-1 [53], poliovirus [54], adenovirus [53], Epstein-Barr virus [55], Mayaro virus [56], Japanese encephalitis virus [57], respiratory syncytial virus [58], and HCV [59,60]. Its antiviral activity mode was studies in a few cases.…”
Section: Antiviral Medicinal Plants and Phytochemicalsmentioning
confidence: 99%
“…Quercetin, an aglycone of rutin, is a phytochemical abundant in plants and may diminish the replication of many viruses: highly pathogenic influenza virus [50], rhinovirus [51], dengue virus type-2 [52], HSV-1 [53], poliovirus [54], adenovirus [53], Epstein-Barr virus [55], Mayaro virus [56], Japanese encephalitis virus [57], respiratory syncytial virus [58], and HCV [59,60]. Its antiviral activity mode was studies in a few cases.…”
Section: Antiviral Medicinal Plants and Phytochemicalsmentioning
confidence: 99%
“…Quercetin 3-␤-O-D-glucoside (Q3G), for example, is a natural derivative of quercetin that contains a glucoside molecule, and this has been shown to enhance the solubility and bioavailability of the compound when ingested (16). Although much research on quercetin and its derivatives has focused on their properties as potential therapeutic agents against cancer and inflammatory diseases and their anti-metabolic disease effects (17), recent studies have also demonstrated antiviral activity against a wide variety of viruses, including influenza virus, Chikungunya virus, Epstein-Barr virus, hepatitis C virus, and Mayaro virus (18)(19)(20)(21)(22). While a detailed mechanism of action remains undefined, it has been proposed that quercetin and its derivatives affect a step in the viral entry process.…”
mentioning
confidence: 99%
“…Other research shows that quercetin inhibits tyrosine kinase, one of the major enzymes associated with cancer and helps flush cancerpromoting chemicals such as BPA (Bisphenol-A) from the body. Importantly, quercetin could be an effective antiviral and antitumor agent against Epstein-Barr Virus (EBV) infection and the human carcinomas it is involved with [3]. Quercetin induces signal transductions to stimulate apoptosis and induces EBV gene transcription; quercetin-induced apoptosis appears to prevent EBV infection.…”
Section: Quercetinmentioning
confidence: 99%
“…Found in red wine, red grapes, and dark berries, resveratrol inhibits cancer by reducing cell proliferation and metastasis and by inducing apoptosis [4]. In particular, resveratrol acts against several genes that promote prostate, colorectal, and other cancers [5].…”
Section: Resveratrolmentioning
confidence: 99%